Lightwave engineering - Kokubun, Yasuo (Optical science and engineering (CRC Press), 2013)
Suitable as either a student text or professional reference, Lightwave Engineering addresses the behavior of electromagnetic waves and the propagation of light, which forms the basis of the wide-ranging field of optoelectronics. Divided into two parts, the book first gives a comprehensive introduction to lightwave engineering using plane wave and then offers an in-depth analysis of lightwave propagation in terms of electromagnetic theory. Using the language of mathematics to explain natural phenomena, the book includes numerous illustrative figures that help readers develop an intuitive understanding of light propagation. It also provides helpful equations and outlines their exact derivation and physical meaning, enabling users to acquire an analytical understanding as well. After explaining a concept, the author includes several problems that are tailored to illustrate the explanation and help explain the next concept. The book addresses key topics including fundamentals of interferometers and resonators, guided wave, optical fibers, and lightwave devices and circuits. It also features useful appendices that contain formulas for Fourier transform, derivation of Green's theorem, vector algebra, Gaussian function, cylindrical function, and more. Ranging from basic to more difficult, the book's content is designed for easily adjustable application, making it equally useful for university lectures or a review of basic theory for professional engineers.